Composição bromatológica e perfil fermentativo da cana-de-açúcar in natura e ensilada hidrolisada com cal virgem - Gregório, Hirla Carneiro dos Santos (2008)
The objective of the present work was to evaluate the effects of different levels (0; 1; 1,5 and 2%) of calcium oxide (CaO) and different hydrolysis time (0, 6, 12, 24 and 48 hours) on the fresh and ensiled sugarcane bromatological composition and on its fermentative perfile. The present work was carried out in a completely randomized experimental design with three replicates per treatment and variance analyses was made with Sisvar program (Tukey Test at 5% of significance). Amounts of sugarcane (IAC 86-2480) were treated with 0; 1; 1,5 and 2% of CaO and samples were collected of each treatment after 0, 6, 12, 24 and 48 hours of CaO addition. Part of treated sugarcane was ensiled in experimental silos which were opened 30 days later. The following variables were analyzed: dry mater (DM), crude protein (CP), crude fiber (CF), acid detergent fiber (ADF), neutral detergent fiber (NDF), liginin (LIG), etereo extract (EE), mineral material (MM), not nitrogen extract (NNE), phosphor (P), calcium (Ca), cellulose ( CEL), hemicellulose (HEM), total digestive nutrients (TDN), volatile fatty acid (VFA), lactate, amoniacal nitrogen (N-NH3) and pH. To fresh sugarcane the treatment with 1% of CaO was able to reduce CF, ADF and NDF and to increase MM, Ca and P, on time 0. After 6 h of hydrolysis with 1; 1,5 or 2% of CaO LIG was reduced and after 24h DM was increased and CEL and HEM were reduced. To ensiled sugarcane the treatment with 1 and 1,5% of CaO was able to increase DS, MM and NNE and to reduce NDF, ADF, LIG, CEL and HEM. Addition of CaO essentiality on higher levels was able to reduce acetic acid concentration and to increase propionic, butyric and lactic acid concentrations and to increase N-NH3 and pH. Higher levels of CP were observed for the non additived forage.